Digenea of Hoplias intermedius and Hoplias malabaricus (Actinopterygii, Erythrinidae) from upper São Francisco River, Brazil - Costa,Danielle Priscilla Correia (2015)
A total of 103 specimens of Hoplias intermedius (Günther, 1864) and 86 specimens of H. malabaricus (Bloch, 1794) from the upper São Francisco River, State of Minas Gerais were collected between April 2011 and August 2013, and their parasitic fauna were investigated. Four species of Digenea were found: metacercariae of Austrodiplostomum sp., and Ithyoclinostomum sp.; and adult specimens of Phyllodistomum spatula Odhner, 1902, and Pseudosellacotyla lutzi (Freitas, 1941) Yamaguti, 1954. The prevalence of the metacercariae was higher than that of the adult digeneans of erythrinids from the upper São Francisco River as a result of piscivorous feeding habits of these adult erythrinids. The presence of metacercariae and adult digeneans indicate that they act as intermediate and definitive hosts, respectively, in their biological cycles. Hoplias intermedius is a new host for the four species of Digenea, and the São Francisco River basin is a new location for the known geographical distributions of P. spatula and P. lutzi.